Developing a Stem Learning Project Model For Artificial Intelligence Courses - ., Rahmiati; Jalinus, Nizwardi; Effendi , Hansi; Melyanti, Rika (Journal of Ecohumanism, 2024)
This study investigates the development of the STEM Learning Project model in artificial intelligence courses to enhance critical thinking skills by training students to analyze problems deeply and find effective solutions, as well as improve technical skills in machine learning, which include algorithms, classification techniques, regression, and clustering. Students possess good conceptual understanding and thinking abilities, but these do not always develop well. To address these challenges, this study introduces the STEM Learning Project model and finds that integrating STEM with project-based learning can increase student engagement and encourage critical and creative thinking. The syntax of this model, derived from existing project-based learning and STEM models, consists of 7 steps: 1) Formulating expected learning outcomes, 2) Determining application-based groups, 3) Planning and designing the project, 4) Performing project tasks and focusing on problems, 5) Testing products and presenting, 6) Evaluation and reflection, 7) Reward. The STEM Learning Project Model offers a promising approach to enhance student learning in artificial intelligence courses. By combining the strengths of STEM and project-based learning, this model can effectively develop students’ critical thinking, problem-solving and technical skills. Future research could explore the long-term impact of this model on student achievement and professional development.